2005
DOI: 10.1016/j.seizure.2005.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of levetiracetam: An add-on trial in children with refractory epilepsy

Abstract: The aim of this multicentric, prospective and uncontrolled study was to evaluate the efficacy and safety of levetiracetam in 110 children with refractory epilepsy, of whom 21 were less than 4 years old. After a median follow-up period of 7 months, levetiracetam administration was effective (responders with >50% decrease in seizure frequency) in 39% of children, of whom 10 (9%) became seizure-free. The efficacy was higher in patients with localization-related epilepsy (58% of responders) than in those with gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
72
0
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 25 publications
9
72
0
10
Order By: Relevance
“…They believed that mental retardation and physical handicap among their studied population played a role as a risk factor for experiencing somnolence during LEV treatment (2). It was the most common side effect reported by the seven of the reviewed articles (2, 10, 11) Behavioral and emotional changes were also reported as the most common cause of withdrawal of LEV (2,11,17,28). Younger patients were reported to be more susceptible to side effects, specially behavioral and emotional changes compared to the large phase III studies in adults (19,29,30).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…They believed that mental retardation and physical handicap among their studied population played a role as a risk factor for experiencing somnolence during LEV treatment (2). It was the most common side effect reported by the seven of the reviewed articles (2, 10, 11) Behavioral and emotional changes were also reported as the most common cause of withdrawal of LEV (2,11,17,28). Younger patients were reported to be more susceptible to side effects, specially behavioral and emotional changes compared to the large phase III studies in adults (19,29,30).…”
Section: Discussionmentioning
confidence: 96%
“…Kanemura et al reported the response rate of 54.1% (16). Grosso et al reported that levetiracetam administration was effective (responders with > 50% decrease in seizure frequency) in 39% of children, of whom 10 (9%) became seizure-free (11). The study by Lagae et al showed seizure frequency reduction of more than 50% in 47% of children very early after introducing the LEV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing the dose of CLB dose was effective for seizure control and NCSE cessation, although benzodiazepines have been reported to occasionally aggravate tonic seizures [1,10]. The major side effects of LEV have been reported to be mostly mild and transient in nature, and include irritability, aggression and somnolence [3][4][5][6]10]. Recently, however, some patients with refractory childhood epilepsy (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, levetiracetam (LEV) is novel anticonvulsants with diminished risks for harmful risks for drug-drug interactions because of its lack of interference with the metabolism of other drugs [3][4][5][6]. Its efficacy and tolerability with regard to improvement in patient' QoL and seizure-control in various refractory epilepsies, including LGS, have been evaluated in several reports [5,7,8].…”
Section: Introductionmentioning
confidence: 99%